The Role of Digital-Based Islamic Microfinance in Empowering the Creative Economy: A Case Study of MSMEs in Cirebon Regency - Mariyah Ulfah (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
Digital transformation is reshaping how creative-economy MSMEs access finance and markets, yet rising platform fees and digital-security risks can undermine fragile margins. This study examines the role of digital-based Islamic microfinance in empowering creative-economy MSMEs in Cirebon Regency, Indonesia. The research applies a qualitative case study design. Data were collected through semi-structured in-depth interviews, limited observation, and document review with MSME owners/managers and LKMS/BMT informants, selected via purposive and snowball sampling. An iterative thematic analysis was used to develop themes. Findings reveal three interrelated mechanisms. First, fit-for-purpose digitization strengthens QRIS transaction traceability and digital bookkeeping, building digital trust that functions as “new collateral” for financing access. Second, platform cost pressures and algorithmic visibility push MSMEs to rebalance marketing toward owned channels to protect margins. Third, a hybrid of human touch and data driven monitoring improves risk mitigation through early warning signals, ethical restructuring, and debt-literacy support. The study advances a hybrid digital–human empowerment model for Islamic microfinance and highlights governance conditions needed to avoid exclusion and overload. Future research should compare subsectors and test fairness in credit scoring across providers.